2007
DOI: 10.1097/fpc.0b013e32801152c2
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and haplotyping of CYP2C19 functional alleles on thin-film biosensor chips

Abstract: This assay can be applied in pharmacogenomic studies in both basic research and clinical laboratories. It is also an ideal technology for pharmacogenomic tests in both developed and developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…As an supplemental step in our assessment of panel performance in this study, we compared the allele frequencies observed here with reference allele frequencies abstracted from multiple sources including the primary literature, The International HapMap Project, 1000 Genomes Project (Pilot 1 Low Coverage Panel), dbSNP, PharmGKB, the Environmental Genome Project, and SNP500Cancer [17 - 22]. Of the 173 diallelic, non-CNV markers targeted by the panel, we were able to abstract allele frequencies from European-descent populations for 109 (63%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an supplemental step in our assessment of panel performance in this study, we compared the allele frequencies observed here with reference allele frequencies abstracted from multiple sources including the primary literature, The International HapMap Project, 1000 Genomes Project (Pilot 1 Low Coverage Panel), dbSNP, PharmGKB, the Environmental Genome Project, and SNP500Cancer [17 - 22]. Of the 173 diallelic, non-CNV markers targeted by the panel, we were able to abstract allele frequencies from European-descent populations for 109 (63%).…”
Section: Resultsmentioning
confidence: 99%
“…Tests of HWE for triallelic SNPs were calculated manually using Pearson’s chi-squared test. ADME Core Panel marker allele frequencies for comparison with the present study were abstracted from the primary literature, The International HapMap Project, 1000 Genomes Project, dbSNP, PharmGKB, the Environmental Genome Project, and SNP500Cancer [17 - 22]. All frequencies were selected from populations of European-descent, similar to the study population described here.…”
Section: Methodsmentioning
confidence: 99%
“…Thin-film biosensor chips are capable of transducing specific molecular interactions into signals that can be visualized by the naked eye or by simple digital-imaging systems because mass deposited on the thin-film surface by enzymatic catalysis alters the wavelength of light reflected by the optical layer resulting in a perceived colour change on the surface [41]. The assay has been described for SNP detection for several animal and plant species and is reported to be robust, exhibit high sensitivity and specificity, and is flexible from low to high throughput [4244]. We are currently examining the feasibility of using this platform for a multiplexed version of the VPMT.…”
Section: Summary and Future Developmentmentioning
confidence: 99%
“…The promoter SNPs were genotyped on thin-film biosensor chips using technology described previously (Nakamoto et al, 2007). Sequences for capture probes (P1) and detection probes (P2) are listed in Supplemental Table S3.…”
Section: Methodsmentioning
confidence: 99%